Interleukin genes and associations with colon and rectal cancer risk and overall survival1. Issue 4 (26th June 2012) - Bondurant, Kristina L.; Lundgreen, Abbie; Herrick, Jennifer S.; Kadlubar, Susan; Wolff, Roger K.; Slattery, Martha L.
Abstract Interleukins are a group of cytokines that contribute to growth and differentiation, cell migration, and inflammatory and anti‐inflammatory responses by the immune system. In our study, we examined genetic variation in genes from various anti‐inflammatory and proinflammatory interleukins to determine association with colon and rectal cancer risk and overall survival. Data from two population‐based incident studies of colon cancer (1, 555 cases and 1, 956 controls) and rectal cancer (754 cases and 954 controls) were used. After controlling for multiple comparisons, single nucleotide polymorphisms (SNPs) from four genes, IL3, IL6R, IL8, IL15, were associated with increased colon cancer risk, and CXCR1 and CXCR2 were significantly associated with increased rectal cancer risk. Only SNPs from genes within the IL‐8 pathway (IL8, CXCR1 and CXCR2) showed a significant association with both colon and rectal cancer risk. Several SNPs interacted significantly with IL8 and IFNG SNPs and with aspirin/non‐steroidal anti‐inflammatory drug (NSAID), cigarette smoking, estrogen use and BMI. For both colon and rectal cancer, increasing numbers of risk alleles were associated with increased hazard of death from cancer; the estimated hazard of death for colon cancer for the highest category of risk alleles was 1.74 (95% confidence interval [CI] 1.18–2.56) and 1.96 (95% CI 1.28–2.99) for rectal cancer. These data suggest that interleukin genes play a role in risk and overall survival for colon and rectal cancer.